Gastroesophageal Stents for the Management of Post Sleeve Gastrectomy Leakage: Interventional Radiology Experience - Abdulmajeed Bin Dahmash; Mohammad Arabi; Aljabriyah Alfutais; Mohammed A. Alswayah; Shaker Alshehri; Refaat Salman; Yousof Al Zahrani; Mohammed Almoaiqel (The Arab Journal of Interventional Radiology)
Objective The aim of this study was to assess the efficacy and safety of retrievable, self-expandable gastroesophageal stents to manage gastric leaks post sleeve gastrectomy by interventional radiology (IR). Methods This is a retrospective study of patients with gastric leaks post sleeve gastrectomy who were managed with gastroesophageal stent placement. The diameters of the stents ranged from 23 to 30 mm and the lengths 12.5 to 24 cm. Results Thirty-one patients (mean age, 32.4 ± 7.97 years) were included in the study, and 46 stents were placed. The total average stenting time was 59.1 ± 35.5 days. Leakage resolved in 93.5% of the patients. Thirty-eight (82.6%) of the stents were retrieved by IR, and the remaining stents were retrieved under endoscopic visualization. Stricture occurred as a complication in four patients: three of which were treated with stenting (one by IR and two by endoscopy) and one required esophagoplasty. Six patients experienced stent migration, three of which underwent stent adjustment, while the remaining three underwent stent reinsertion Conclusion Gastroesophageal stent placement by IR for gastric leaks post sleeve gastrectomy is safe and effective in our study.